Tax Compliance Drivers In Indonesian SMEs Based On Knowledge Awareness And Religious Commitment - Nurul Audry Paradigma LR; Viola Syukrina E Janrosl (International Journal of Education Management and Religion, 2026)
This study aims to analyze the influence of tax knowledge, awareness, and religiosity on taxpayer compliance among small and medium enterprises (SMEs) in Indonesia. The study adopts a quantitative approach using primary data collected through questionnaires distributed to SME taxpayers. Data analysis was conducted using multiple linear regression with a significance level of 0.05. The results of the study show that tax knowledge has a t-value of 2.279 greater than the t-table value of 1.98498 and a significance level of 0.000 < 0.05, indicating that tax knowledge partially affects taxpayer compliance. The awareness variable also shows a t-value of 2.680 > 1.98498 with a significance level of 0.000 < 0.05, meaning that taxpayer awareness has a significant influence on compliance. Furthermore, the religiosity variable has a t-value of 2.988 > 1.98498 and a significance level of 0.000 < 0.05, suggesting that religiosity has a positive and significant effect on taxpayer compliance. These findings imply that increasing taxpayers' understanding of taxation, enhancing their awareness of tax obligations, and strengthening their religious values can significantly improve compliance levels. The study contributes to the development of behavioral tax compliance models by highlighting the role of internal factors such as knowledge, awareness, and religiosity. The results are expected to provide insights for policymakers and tax authorities in designing effective strategies to foster voluntary compliance among SME taxpayers in Indonesia.